On the areas under the oscillatory curves - Smirnov, Sergey (Nonlinear Analysis: Modelling and Control, 2017)
We prove that the third-order Emden–Fowler-type equation has oscillatory non-extendable solutions with specific behavior of antiderivative.
Keywords: third-order Emden–Fowler-type equation; oscillatory behavior of solutions; self-similar solutions; matching of the area